Multi-isotope analysis of the human skeletal remains from Blair Atholl, Perth and Kinross, Scotland. (2021) - Czére, Orsolya; Fawcett, Jovita; Evans, Jane; Sayle, Kerry; Müldner, Gundula; Hall, Mark; Will, Bob; Mitchell, Juliette; Noble, Gordon; Britton, Kate
No abstract available